Therapeutic Methods Used by the Ancient Population of North Africa - Sandouk, Setti (Jordan Journal for History and Archaeology, 2023)
This article discusses the healing practices that the ancient inhabitants of North Africa used. Those practices developed from many attempts and experiments going back to the prehistoric period that were derived from the natural environment in which people lived, where they had accumulated knowledge. Plants and herbs constituted the main source of medicine, which included wild plants such as silphium and cultivated plants such as vegetables and fruits, along with magical practices and rituals such as carrying amulets and talismans, reciting incantations, cauterizing, and using blessed soil and blood. The ancient population of North Africa attributed the cause of some diseases to the wrath of the gods and spirits. Patients were obliged to gain their sympathy and receive their blessing in order to regain their health, through some offerings and supplications. They form the basis of therapeutic prescriptions, promoted by the god of healing Eshmoun, who was brought by the Phoenicians to the ancient Maghreb, and parallels the Roman god Aesculapius, along with the goddess Hygia and the local Libyan god Macurgum. Mineral baths also played an important role in healing. Although the oldest evidence for the use of its hot mineral baths dates to the Roman period, that does not negate its use by the local population earlier. Stones and minerals, such as salt, vermilion stone, and hematite, along with sea sponges were also used to relieve health problems.